Simple one-pot synthesis and high-resolution patterning of perovskite quantum dots using a photocurable ligand - Oh, Byeong M.; Jeong, Yongcheol; Zheng, Jian; Cho, Na Young; Song, Myungkwan; Choi, Jin Woo; Kim, Jong H. (Chemical Communications, 2021)
In this study, we report a UV-light-curable azide ligand (AzL) for the micro-patterning of PeQDs. AzL can be attached to the surface of the PeQDs during their synthesis without additional ligand exchange. Using the AzL-grafted CsPbBr3 PeQDs, high-color-purity 240 × 240 μm2 square-shaped patterns were successfully fabricated using UV light irradiation, which corresponds to a resolution of >50 pixels per inch.
Keywords: Azide ligands; Color purity; High-resolution patterning; Ligand exchanges; Micro patterning; One-pot synthesis; Photocurable; Shaped pattern; Simple++; UV-light